Maternal and neonatal outcomes after antenatal corticosteroid administration for PPROM at 32 to 33 6/7 weeks gestational age*. (18th July 2017) - Sheibani, Lili; Fong, Alex; Henry, Dana E.; Norton, Mary E.; Truong, Yen N.; Anyikam, Adanna; Laurent, Louise C.; Rao, Rashmi; Wing, Deborah A.; ,
Abstract: Background : Preterm Premature Rupture of Membranes (PPROM) precedes many deliveries and experts agree with expectant management until 34 weeks gestation. However, there is controversy regarding the gestational age (GA) for administration of corticosteroids. Study design : We performed a retrospective cohort study in the University of California Fetal Consortium (UCfC). We searched available charts of singleton pregnancies with PPROM between 32 and 33 6/7 weeks GA. Outcomes from the groups were analyzed. Results : Of 191 women with PPROM at 32 to 33 6/7 weeks, 150 received corticosteroids. The median GA at admission was earlier for the exposed versus unexposed group (32 4/7 versus 33 0/7 weeks, respectively, p  = 0.001). The mean GA at delivery in the exposed was 33 2/7 (32 0/7 to 35 0/7) weeks versus 33 5/7 (32 0/7 to 36 1/7) weeks in the unexposed ( p  = 0.001). There was no difference in chorioamnionitis or RDS. Conclusion : In women with PPROM at 32 to 33 6/7 weeks, our data suggests that corticosteroids are associated with similar outcomes despite earlier GA at delivery and no differences in major morbidities. A larger prospective study is needed to determine if the benefit of corticosteroids outweighs the potential risks in PPROM.